Epidemiological, clinical and therapeutic profile of the umbilical cord prolapse at the Befelatanana University Hospital Centre of Obstetric Gynecology in Antananarivo, Madagascar - R., Randriamahavonjy; M., Rakotonirina Andriamaro; T., Ratsiatosika Andriamanetsiarivo; I., Housni; A., Abasse B.; F., Rakototiana A; R., Andrianampanalinarivo H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Umbilical cord prolapse is a major obstetrical emergency that threatens the fetal prognosis during labor. The objective of this study was to describe the epidemiologic and clinical profile of pulsatile cord prolapse at the Befelatanana University Hospital of Obstetric Gynecology. Methods: It is about a retrospective cross-sectional study conducted at the Befelatanana University Hospital of Obstetrics and Gynecology in Antananarivo over a period of 3 years, from January 1st, 2012 to December 31st, 2014. We have identified all cases of umbilical cord prolapse. We studied obstetric, neonatal and maternal parameters. Results: We found 70 cases of pulsatile umbilical cord prolapse, a prevalence of 0.28% of deliveries. The average age of the patients was 28 ± 3.2 years with extremes ranging from 18 to 43 years. Multiparous women predominated with (51.43%) Pregnancy was long term, with 71.43% of cases associated with placenta praevia, lateral prolapse of the limb, long cord and contracted pelvis. The prolapse of the cord was 1st degree with 44.29% of cases. All patients had received (100%) of oxygen therapy. Almost all patients were caesarized (95.71%). Neonatal complications were represented by admission to neonatal intensive care unit (32.86%), perinatal asphyxia (31.43%), prematurity (28.57%), neonatal infection (4.29%) and neonatal death (10%). Conclusions: The umbilical cord prolapse is relatively rare. Fetal extraction in the shortest possible time, especially when the cord is externalized, which is the main determining factor of neonatal prognosis.